2019
DOI: 10.31883/pjfns/113152
|View full text |Cite
|
Sign up to set email alerts
|

Lemongrass (Cymbopogon citratus) Essential Oil: Extraction, Composition, Bioactivity and Uses for Food Preservation – a Review

Abstract: , and the others in South Asia. Cymbopogon exuosus and Cymbopogon citratus represent the two major species vastly cultivated for their essential oils in different regions of the world. C. citratus is known by numerous international common names, such as West Indian lemon grass or lemon grass (English), citronelle or verveine des indes (French), hierba limon or zacate de limón (Spanish), xiang mao (Chinese), capimcidrao or capim-santo (Portuguese), and locally there are identi ed more than 28 indigenous names f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 93 publications
1
71
0
3
Order By: Relevance
“…Hal ini dapat disebabkan karena selain dipengaruhi jenis bakteri, aktivitas antibakteri juga dipengaruhi jenis komponen yang ada di dalamnya. Citral banyak berperan pada bioaktivitas minyak sereh dapur seperti antibakteri (Ganjewala, 2009) (Han Lyn and Nur Hanani, 2020) (Yang and Song, 2016) (Hosseinzadeh et al 2020) (Majewska et al 2019) dan antijamur (Ganjewala, 2009). Minyak sereh dapur memiliki aktivitas antibakteri terhadap bakteri gram positif dan bakteri gram negatif, baik dalam bentuk minyak maupun dalam bentuk uap (Argyropoulou et al 2007) (Yunilawati et al 2020.…”
Section: Aktivitas Antibakteriunclassified
See 1 more Smart Citation
“…Hal ini dapat disebabkan karena selain dipengaruhi jenis bakteri, aktivitas antibakteri juga dipengaruhi jenis komponen yang ada di dalamnya. Citral banyak berperan pada bioaktivitas minyak sereh dapur seperti antibakteri (Ganjewala, 2009) (Han Lyn and Nur Hanani, 2020) (Yang and Song, 2016) (Hosseinzadeh et al 2020) (Majewska et al 2019) dan antijamur (Ganjewala, 2009). Minyak sereh dapur memiliki aktivitas antibakteri terhadap bakteri gram positif dan bakteri gram negatif, baik dalam bentuk minyak maupun dalam bentuk uap (Argyropoulou et al 2007) (Yunilawati et al 2020.…”
Section: Aktivitas Antibakteriunclassified
“…Geraniol dalam minyak sereh dapur juga dilaporkan memiliki aktivitas dalam melawan beberapa bakteri patogen (Ternus and Zanetti, 2015). (Hosseinzadeh et al 2020) (Majewska et al 2019) dan antijamur (Ganjewala, 2009). Minyak kulit jeruk purut memiliki zona hambatan yang kuat pada S. aureus NBRC 100910 namun lemah/tidak ada pada E. coli NBRC 3301.…”
Section: Aktivitas Antibakteriunclassified
“…The chemical composition of substances from cellular metabolism, especially those from secondary metabolism, varies widely. According to Majewska et al (2019), genetic-environmental factors, crop management, harvesting and essential oils extracting methods have a direct or indirect influence on the oil obtained, especially for the lemongrass oil. Thus, it should be noted that the efficiency of antimicrobial control may be associated with the batch of oil extracted.…”
Section: Effect Of Essencial Oils On the Growth Controlo Of Isolatesmentioning
confidence: 99%
“…Lemongrass scientifically is known as Cymbopogon citratus and it belongs to the Poaceae family which counts more than 635 genera and 9000 species (Majewska et al, 2019). C. citratus is widely spread globally.…”
Section: Introductionmentioning
confidence: 99%
“…C. citratus is widely spread globally. More than 140 species of Cymbopogon, 52 of them grow in Africa, 45 in India, 6 in Australia, 6 in South America, 4 in Europe (only in Montenegro), 2 in North America, and the others in South Asia (Majewska et al, 2019). The genus Cymbopogon has been reviewed comprehensively in several articles (Avoseh et al, 2015;Haque et al, 2018).Nambiar and Matela (2012) reported that lemongrass grows well in both tropical and subtropical climates with around 900m elevation.…”
Section: Introductionmentioning
confidence: 99%